Israeli media’s noopolitik strategy: Ynetnews’ framing of Hamas in the Israeli-Palestine conflict - Wafi, Fadhlil; Aqil, Muhammad; Kohar, Wakidul; Zaini, Maryolanda (Faculty of Communications Science, Dr. Soetomo University, 2025)
The online news coverage regarding the ongoing Gaza conflict published by Ynetnews extends beyond information dissemination but also includes information frames that align with Israel's noopolitik interests. However, this theme remains under academic research as literature regarding this study remains scarce. This study is also based on the question: how Ynetnews use media framing as an Israeli noopolitik tool to create a negative image of Hamas in the ongoing hostilities between Hamas and Israel. The data in this study was collected by analysing twenty-seven (27) news articles published on Ynetnews website using the keyword ‘Israel-Palestine Conflict’ from 10 December 2023 to 14 January 2024. This study employed the framing analysis method of Zhongdang Pan and Gerald M. Kosicky to uncover and answer the research questions. The study highlights two important findings on Israel’s noopolitik strategy: The first strategy is made through the consistent portrayal of Hamas as a terrorist group as being published by Ynetnews in its online content. Second strategy is by accusing Hamas of playing the victim, which is paradoxically a strategy being projected by Israel.